Pengaruh Manajemen Pemasaran Terhadap Kesiapan Berwirausaha Mahasiswa Tips Semester 7 UIN Sayyid Ali Rahmatullah Tulungagung - Widoningtyas, Larasati (UIR Press, 2024)
This study aims to analyze the influence of marketing management on the entrepreneurial readiness of 7th semester Social Science Education (TIPS) students at Sayyid Ali Rahmatullah State Islamic University of Tulungagung. The research method used is quantitative with a descriptive-correlational design, involving 100 students as samples taken through purposive sampling techniques. Data were collected using a questionnaire consisting of two parts: understanding of marketing management and entrepreneurial readiness. The results of the regression analysis showed that there was a significant influence between marketing management and entrepreneurial readiness, with a coefficient of determination (R²) of 0.45. This indicates that 45% of the variance in entrepreneurial readiness can be explained by the understanding of marketing management. The results also show that students who are active in extracurricular activities and have academic support tend to be more ready to start a business. This study concludes that marketing management plays an important role in preparing students for entrepreneurship and recommends strengthening marketing management material in the entrepreneurship curriculum in universities